Efficacy of the environmentally sustainable microwave heating compared to biocide applications in the devitalization of phototrophic communities colonizing rock engravings of Valle Camonica, UNESCO world heritage site, Italy. (November 2021) - Favero-Longo, S.E.; Matteucci, E.; Pinna, D.; Ruggiero, M.G.; Riminesi, C.
Abstract: The devitalization of lithobionts prior to their removal from engraved rocks is a common conservation practice periodically undertaken in rock art sites. In this study, we assessed in situ the efficacy of three traditional biocides and of an innovative microwave heating system, and compared different application protocols to devitalize foliose and crustose lichens and a cyanobacteria-dominated biofilm on the rock engravings of Valle Camonica (UNESCO site n.94, Italy). The analysis of their vitality and stress responses by monitoring chlorophyll a fluorescence parameters (Fv /Fm, F0, OJIP transient) showed that the common application of biocides by brush is rather ineffective, particularly in the case of the resistant crustose lichens. The heating of rock surfaces to 70 °C for a few minutes by the microwave system caused devitalization of lithobionts to a similar extent as the biocide application with cellulose poultice, which, however, introduced high amounts of chemicals in the environment. The microwave irradiation overcame any lithobiontic stress resistance and avoided useless or excessive spread of biocides, appearing a promising sustainable approach for the parallel conservation of rock art and its surrounding natural environment. Highlights: The efficacy of three biocides and a microwave (MW) heating system was assessed. Poultice application of biocides devitalized lichens and a cyanobacterial biofilm. MW heating to 70 °C accomplished the same effect avoiding the use of chemicals. The application of biocides by brush was ineffective against lichens.